WikiOlapBase: A collaborative tool for open data processing and integration - Bernardo, Pedro M.; Silva, Ismael S.; Barbosa, Glívia A. R.; Coutinho, Flávio R. S.; Barros, Evandrino G. (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC), 2017)
The technological advances have made data sharing and knowledge generation possible in several areas. In order to support information extraction and knowledge generation, several datasets have been made publicly available, giving rise to the concept of open data. However, while such data are available, the processing, visualization, and analysis of them by society, in general, can be considered difficult tasks. Data are available to a great volume, in different files and formats, making it difficult to cross-reference and analyze them to obtain relevant information without the support of appropriate tools. Inspired by this scenario, this paper presents WikiOlapBase, a collaborative tool capable of processing, integrating and making feasible the analysis of open data from different sources, even by people without technical knowledge. WikiOlapBase contributes to the expansion of open data analysis, since it favors a greater information sharing and knowledge dissemination.